Psychological factor in couples with infertility problems - Pacheco Romero, José (2015)
OBJETIVE: To correlate infertility and the psychological factor in infertile couples. DESIGN Descriptive retrospective clinical psychological study of couples with infertility problems. MATERIAL: Twenty-five infertile couples studied through the following instruments: a) interview, b),5pecial card and c) Zung autoevaluation scale. LOCATI0N.- Human Reproduction Service, Edgardo Rebagliati Martins National Hospital, SSPT RESULTS: Emotional area: high levels of anxiety and depression, more in women (70%). Social area: deficit in social life, with performance significantly below previous functional levels, 65% in women, 35% in men. Sexual area: decrease of sexual interest (70% in women, plus vaginismus). CONCLUSIONS: The study of the psychological factor is very important in the evaluation of the infertile couple. We should consider the high prevalence of anxiety, depression and sexual disfunction in the infertile couple, particulary in women.